Everyday stress-induced neurobehavioral dysregulation: therapeutic targets for management with Neurexan - Duller, Stephan; Clarke, Gerard; Herculano-Houzel, Suzana; von Känel, Roland; Kirsch, Peter; Landolt, Hans-Peter; Naschold, Britta; Reber, Stefan O.; Schreiber, Rudy; Walter, Martin; Slavich, George M. (Frontiers in Psychiatry, 2025)
Everyday stress is highly prevalent and can impact human health, performance, well-being, and mortality risk. Despite being widely acknowledged, everyday stress is rarely assessed or treated, highlighting a critical gap in clinical routine. To better understand the relevance of everyday stress for healthcare professionals, we use the Research Domain Criteria (RDoC) framework to link stress neurobiology to its behavioral signs and symptoms. According to RDoC, everyday stress is conceptualized as impacting domains of basic neurobiological functioning. Everyday stress influences two primary domains – the negative valence domain, and arousal and regulatory systems – that can, in turn, lead to mental and physical health problems. Neurexan, a natural multi-component medication, targets these two domains. We review recent data on how Neurexan can mitigate the negative impact of stress on the negative valence domain and regulate arousal, thus helping to restore neurobiological and clinical functioning. This review provides an overview of relevant aspects of stress, mainly everyday stress, and the latest research on Neurexan as a potential option to target everyday stress. More broadly, this work may lead to new methods of assessing and managing everyday stress to improve the psychosocial resilience and well-being of individuals facing difficulty coping with repetitive or chronic stress in their daily lives.